Antioxidant activity of pomegranate peel extract on lipid and protein oxidation in beef meatballs during frozen storage. (July 2017) - Turgut, Sebahattin Serhat; Işıkçı, Fatma; Soyer, Ayla
Abstract: Antioxidant effect of pomegranate peel extract (PE) to retard lipid and protein oxidation in beef meatballs was investigated during frozen storage at − 18 ± 1 °C. Concentrated and freeze dried aqueous extract of pomegranate peel was incorporated into freshly prepared meatball mix at 0.5% and 1.0% concentrations, and compared with 0.01% butylated hydroxytoluene (BHT) and control (without any antioxidant). In PE treated samples, particularly in high PE concentration, peroxide, malondialdehyde and carbonyl formation, loss of total protein solubility and sulfhydryl groups were significantly lower than control after 6 months of storage. A diminution of both myofibrillar (MP) and sarcoplasmic (SP) proteins of high molecular weight was detected after 6 months of the storage according to gel electrophoresis patterns. The 1.0% PE led to maintain colour intensity (C) and hue (h°) value. The results from sensory analyses revealed that PE addition to meatballs was effective on preventing rancid odour formation. Addition of both 0.5 and 1% PE in meatballs reduced lipid and protein oxidation and improved sensory scores. These results indicated that PE was effective on retarding lipid and protein oxidations. Highlights: Concentrated lyophilized aqueous extract of pomegranate peel (PE) was prepared. PE was used to improve the oxidative stability of frozen meatballs. Lipid and protein oxidations were strongly inhibited by PE addition. Antioxidative effect enhanced as PE concentration increased.